2009
DOI: 10.1111/j.1439-0272.1981.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Progressive Motility Sustaining Factor (PMSF) in Human Epididymis

Abstract: Zusammenfassung Das Vorhandensein eines Faktors, der die progressive Motilität der Spermatozoen unterstützt, im menschlichen Nebenhoden In Extrakten von menschlichen Nebenhoden konnte ein Faktor ermittelt werden, der die progressive Motilität der Spermatozoen unterstützt. Mittels dieses Faktors ließ sich sowohl bei Männern mit Oligozoospermie als auch mit Asthenozoospermie eine signifikante Besserung der Motilität der Spermatozoen hervorrufen. Es kann gezeigt werden, daß der Effekt dieses Faktors (PMSF) durch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As reviewed in the Introduction Section, earlier investigators have reported the occurrence of multiple sperm motility regulating undefined protein factors in the male reproductive fluids (Morton and Chang, 1973;Gaur and Talwar, 1975;Acott and Hoskins, 1978;Hoskins et al, 1978;Sheth et al, 1981;Pinto et al, 1984;Jaiswal and Majumder, 1998;Ding et al, 2007;Tso and Lee, 2008). However, none of these motility proteins have been purified to apparent homogeneity and characterized.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As reviewed in the Introduction Section, earlier investigators have reported the occurrence of multiple sperm motility regulating undefined protein factors in the male reproductive fluids (Morton and Chang, 1973;Gaur and Talwar, 1975;Acott and Hoskins, 1978;Hoskins et al, 1978;Sheth et al, 1981;Pinto et al, 1984;Jaiswal and Majumder, 1998;Ding et al, 2007;Tso and Lee, 2008). However, none of these motility proteins have been purified to apparent homogeneity and characterized.…”
Section: Discussionmentioning
confidence: 92%
“…The biochemical mechanism of sperm forward initiation in epididymis and its regulation is largely unknown. As reviewed earlier (Mandal et al, 1989;Majumder and Mandal, 1992;Majumder et al, 2001), early workers have reported the occurrence of various types of uncharacterized motility regulating protein factors in male reproductive fluids/ reproductive organs (Morton and Chang, 1973;Gaur and Talwar, 1975;Sheth et al, 1981;Tso and Lee, 2008). Hoskins and his associates Hoskins et al, 1978) have developed a novel in vitro model that permitted initiation of forward motility in the immature (immotile) sperm derived from bovine caput-epididymis when incubated in presence of epididymal plasma/seminal plasma and theophylline.…”
mentioning
confidence: 94%
“…This characteristic of forward motility of male gamete cells is primarily achieved during the epididymal transit [3] ; however the cells attain the ultimate kinetic potential inside the female genital tract [4] . Reports of various types of extracellular sperm motility promoting factors in male reproductive fluids and blood serum of different animals, as well as human, have been part of the scientific literature for the last four decades [2] , [5] , [6] , [7] , [8] , [9] , [10] . But, none of these motility-regulatory entities were sufficiently purified and characterized.…”
Section: Introductionmentioning
confidence: 99%